Chitosan/poly(ethylene glycol)/hyaluronic acid biocompatible patches obtained by electrospraying - (:unkn) unknown (IOP PUBLISHING LTD, 2018)
Electrospray is a promising technique to scale-up production of microparticles and nanoparticles. In this study, electrospraying was used in order to produce candidate biopatches (CPH) by using chitosan, poly (ethylene glycol) (PEG) and hyaluronic acid (HA). Four different ratios of polymer blend compositions (CPH1, CPH2, CPH3 and CPH4) were tested by dissolving in 2% acetic acid solution (Ac.A.). The HA amount in each blend was kept the same to designate the optimum surface with different chitosan/PEG ratios for electrospray process. Fourier-transform infrared (FTIR) microscopy, scanning electron microscopy (SEM), and atomic force microscopy (AFM) studies showed that obtained patches had highly adhesive surfaces with the aid of heterogeneously distributed micro- and nano-particles. Additionally, video images of FTIR microscopy and AFM images proved that all surfaces have similar heterogeneity except CPH2. The most homogenous surface was obtained by CPH3. Patches were directly subjected to antibacterial tests against ten different types of gram positive and gram negative bacteria using disc diffusion assay (Kirby-Bauer method). Extraordinarily there was no antibacterial property of patches coated with microparticles. Finally, biocompatibility studies were performed by using mouse fibroblast L929 cell lines (ATTC number CCL-1) to test cell adhesion and proliferation properties of the patches. Results of 72 h viability tests proved the electrospray of ternary blends had displayed good biocompatibility; in particular, CPH3 had the highest cell viability.
Keywords: chitosan; hyaluronic acid; nanoparticle; biocompatibility; electrospray; poly(ethylene glycol); HYALURONIC-ACID; DRUG-DELIVERY; BLEND FILMS; NANOPARTICLES; MUCOADHESIVE; HYDROGEL; THERAPY; RELEASE; IMPACT; CANCER